Does frequent residential mobility in early years affect the uptake and timeliness of routine immunisations? An anonymised cohort study. Issue 15 (4th April 2016) - Hutchings, Hayley A.; Evans, Annette; Barnes, Peter; Healy, Melanie A.; James-Ellison, Michelle; Lyons, Ronan A.; Maddocks, Alison; Paranjothy, Shantini; Rodgers, Sarah E.; Dunstan, Frank
Abstract: Background: There are conflicting findings regarding the impact of residential mobility on immunisation status. Our aim was to determine whether there was any association between residential mobility and take up of immunisations and whether they were delayed in administration. Methods: We carried out a cohort analysis of children born in Wales, UK. Uptake and time of immunisation were collected electronically. We defined frequent movers as those who had moved: 2 or more times in the period prior to the final scheduled on-time date (4 months) for 5 in 1 vaccinations; and 3 or more times in the period prior to the final scheduled on-time date (12 months) for MMR, pneumococcal and meningitis C vaccinations. We defined immunisations due at 2–4 months delayed if they had not been given by age 1; and those due at 12–13 months as delayed if they had not been given by age 2. Results: Uptake rates of routine immunisations and whether they were given within the specified timeframe were high for both groups. There was no increased risk (odds ratios (95% confidence intervals) between frequent movers compared to non-movers for the uptake of: primary MMR 1.08 (0.88–1.32); booster Meningitis C 1.65 (0.93–2.92); booster pneumococcal 1.60 (0.59–4.31); primary 5 in 1 1.28 (0.92–1.78); and timeliness: primary MMR 0.92 (0.79–1.07); booster Meningitis C 1.26 (0.77–2.07); booster pneumococcal 1.69 (0.23–12.14); and primary 5 in 1 1.04 (0.88–1.23). Discussion: Findings suggest that children who move home frequently are not adversely affected in terms of the uptake of immunisations and whether they were given within a specified timeframe. Both were high and may reflect proactive behaviour in the primary healthcare setting to meet Government coverage rates for immunisation.